2019
DOI: 10.1121/1.5098770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ripple repetition rate on discrimination of ripple glide direction and the detection of brief tones in spectro-temporal ripple noise

Abstract: The effect of temporal repetition rate R on the discrimination and internal representation of stimuli with spectro-temporal ripples was examined. Experiment 1 measured the highest ripple density D at which upward- and downward-gliding ripples could be discriminated. Thresholds varied only slightly for R from 2 to 8 Hz, with a median threshold just above 5 ripples/oct. The threshold decreased (worsened) when R was increased to 16 and 32 Hz, suggesting that the limited temporal resolution of the auditory system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The improvement in spatial resolution on the SMRT at conversational loudness would be expected to also be apparent on the STRIPES, which was not the case. This could possibly be explained by the tests measuring different warranted or spurious cues (e.g., loudness cues and noticeable changes in the spectral edges), as has been debated in recent literature (Narne et al 2016; Archer-Boyd et al 2018; Narne et al 2019). It could also signify that the absence of a significant effect on the STRIPES and the small distinguishable effect on the SMRT means that the clinical relevance of the findings is marginal.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in spatial resolution on the SMRT at conversational loudness would be expected to also be apparent on the STRIPES, which was not the case. This could possibly be explained by the tests measuring different warranted or spurious cues (e.g., loudness cues and noticeable changes in the spectral edges), as has been debated in recent literature (Narne et al 2016; Archer-Boyd et al 2018; Narne et al 2019). It could also signify that the absence of a significant effect on the STRIPES and the small distinguishable effect on the SMRT means that the clinical relevance of the findings is marginal.…”
Section: Discussionmentioning
confidence: 99%
“…However, as pointed out by the authors (see Miller et al, 2018), several distinct mechanisms might be conflated by these measurements: broader cochlear filters due to hearing loss as well as deficits related to other processes (that were not engaged with pure tones), such as temporal fine structure (TFS) processing. In relation to the former aspect, some recent studies go as far as suggesting that upward/downward STM discrimination thresholds could serve as a proxy measure for auditory filter bandwidth (BW; Narne et al, 2019Narne et al, , 2020. In addition, it is important to note that these studies have examined factors that limit the ability of HI listeners to detect modulations at threshold, but these factors may differ from those recruited when extracting suprathreshold STMs from modulation noise, such as in the context of Oetjen and Verhey's (2015) masking paradigm.…”
mentioning
confidence: 99%
“…In a spectro-temporal test based on the STRIPES, Narne et al (2018Narne et al ( , 2019 found that the test was not affected by cues related to changes at the spectral edges and, therefore, provided a reliable estimate of frequency resolution as long as the repetition rate did not exceed 8 Hz. With a repetition rate of 5 Hz the STRIPES are expected to be free from cues at the spectral edges.…”
Section: Introductionmentioning
confidence: 99%